Reaction Site Diversity in the Reactions of Titanium Hydrazides with Organic Nitriles, Isonitriles and Isocyanates: Ti==N(α) Cycloaddition, Ti==N(α) Insertion and N(α)--N(β) Bond Cleavage. - Schofield, A; Nova, A; Selby, J; Schwarz, A; Clot, E; Mountford, P (2010)
We report a range of new transformations of the diamide-amine supported Ti==NNPh(2) functional group with a variety of unsaturated substrates, along with DFT studies of the key mechanisms. Reaction of [Ti(N(2)N(py))(NNPh(2))(py)] (4, N(2)N(py)=(2-NC(5)H(4))CMe(CH(2)NSiMe(3))(2); py=pyridine) with MeCN gave the dimeric species [Ti(2)(N(2)N(py))(2){μ-NC(Me)(NNPh(2))}(2)] through a [2+2] cycloaddition process. Reaction of 4 or [Ti(N(2)N(Me))(NNPh(2))(py)] (5, N(2)N(Me)=MeN(CH(2)CH(2)NSiMe(3))(2)) with fluorinated benzonitriles gave the terminal hydrazonamide complexes [Ti(N(2)N(R)){NC(Ar(F(x) ))NNPh(2)}(py)] (R=py or Me; Ar(F(x) )=2,6-C(6)H(3)F(2) or C(6)F(5)). DFT studies showed that this proceeds through an overall [2+2] cycloaddition-reverse cycloaddition, resulting in net insertion of Ar(F(x) )CN into the Ti==N(α) bonds of the respective hydrazides. Reaction of 4 with a mixture of MeCN and PhCCMe gave the metallacycle [Ti(N(2)N(py)){NC(Me)C(Ph)C(Me)NNPh(2)}] by sequential coupling of Ti==NNPh(2) with PhCCMe and then MeCN. A related product, [Ti(N(2)N(py)){NC(Me)C(Ar(F))C(H)NNPh(2)}], was formed by insertion of MeCN into the Ti--C bond of the isolated azatitanacyclobutene [Ti(N(2)N(py)){N(NPh(2))C(H)C(Ar(F))}] (Ar(F)=3-C(6)H(4)F). Reaction of 4 with two equivalents of B(Ar(F(5) ))(3) (Ar(F(5) )=C(6)F(5)) formed the zwitterionic borate [Ti(N(2)N(py)){η(2)-N(NPh(2))B(Ar(F(5) ))(3)}] by electrophilic attack at N(α). Compounds 4 and 5 reacted with tBuNC and/or XylNC (Xyl=2,6-C(6)H(3)Me(2)) to give the N(α)--N(β) bond cleavage products, [Ti(N(2)N(R))(NCNR')(NPh(2))] (R=py or Me; R'=tBu or Xyl), containing metallated carbodiimide ligands. DFT studies of these reactions found an initial addition of RNC across Ti==N(α) followed by N(β) coordination, and finally complete N(α) transfer from the NNPh(2) to the RNC fragment. Reaction of 5 with Ar'NCE (E=O, S, Se; Ar'=2,6-C(6)H(3)iPr(2)) gave the [2+2] cycloaddition products [Ti(N(2)N(Me)){N(NPh(2))C(NAr')O}(py)] and [Ti(N(2)N(Me)){N(NPh(2))C(NAr')E}] (E=S or Se), which did not undergo further transformation of the Ti--N--NPh(2) moiety.